2019
DOI: 10.31227/osf.io/6zqdc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional Disparities of Stunted Toddler in Indonesia

Abstract: Background/Objective: Although there has been a decline in the prevalence of stunting in Indonesia in the past decade, the figure is still the highest among countries in Southeast Asia. This figure varies in 34 provinces. The purpose of the study was to analyze the regional disparity of stunted toddlers in Indonesia. Materials and Methods: The analysis in this study uses data from the 2017 Indonesian Nutritional Status Monitoring (PSG 2017). Multi-stage cluster random sampling was used in the PSG 2017. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
2
27
0
3
Order By: Relevance
“…The analysis also found that toddler's age is a determinant of stunted and severe stunted toddlers. This finding is in line with the results of previous studies in Bangladesh, Ethiopia, Uganda, including Indonesia (10,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The analysis also found that toddler's age is a determinant of stunted and severe stunted toddlers. This finding is in line with the results of previous studies in Bangladesh, Ethiopia, Uganda, including Indonesia (10,(30)(31)(32)(33).…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has found that early-life stunting has adverse functional consequences, including poor cognition and low levels of education. Later as adults will have low wages, lost productivity, and if this is accompanied by weight gain in childhood, will increase the risk of chronic diseases related to nutrition (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data analyzed is aggregate data at a certain group or level, which in this study is the provincial level. The variables in an ecological analysis can be aggregate measurements, environmental measurements, or global measurements (Laksono and Kusrini, 2020). The purpose of the ecological studies is to make biological inferences about effects on individual risk or to make ecological inferences about effects on groups (Morgenstern, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…Oleh karenanya penting untuk menjaga kesehatan jiwa seseorang dimulai dari dia masih bayi. Bayi yang dilahirkan secara normal biasanya memiliki ukurang panjang badan 48-52 cm, ukuran lingkar dada 30-38 cm, dan ukuran lingkar lengan 11-12 cm (Laksono & Kusrini, 2019). Kondisi ini harus dipertahankan sesuai dengan pertumbuhan dan perkembangan agar terhindar dari faktor risiko terhambatnya proses tumbuh kembang.…”
Section: Pendahuluanunclassified